Generating political priority for regulatory interventions targeting obesity prevention: an Australian case study. (March 2017) - Baker, Phillip; Gill, Timothy; Friel, Sharon; Carey, Gemma; Kay, Adrian
Abstract: Effective obesity prevention requires a synergistic mix of population-level interventions including a strong role for government and the regulation of the marketing, labelling, content and pricing of energy-dense foods and beverages. In this paper we adopt the agenda of the Australian Federal Government (AFG) as a case study to understand the factors generating or hindering political priority for such 'regulatory interventions' between 1990 and 2011. Using a theoretically-guided process tracing method we undertook documentary analysis and conducted 27 interviews with a diversity of actors involved in obesity politics. The analysis was structured by a theoretical framework comprising four dimensions: the power of actors involved; the ideas the actors deploy to interpret and portray the issue; the institutional and political context; and issue characteristics. Despite two periods of sustained political attention, political priority for regulatory interventions did not emerge and was hindered by factors from all four dimensions. Within the public health community, limited cohesion among experts and advocacy groups hampered technical responses and collective action efforts. An initial focus on children (child obesity), framing the determinants of obesity as 'obesogenic environments', and the deployment of 'protecting kids', 'industry demonization' and 'economic costs' frames generated political attention. Institutional norms within government effectively selected out regulatory interventions from consideration. The 'productive power' and activities of the food and advertising industries presented formidable barriers, buttressed by a libertarian/neolibertarian rhetoric emphasizing individual responsibility, a negative view of freedom (as free from 'nanny-state' intervention) and the idea that regulation imposes an unacceptable cost on business. Issue complexity, the absence of a supportive evidence base and a strict 'evidence-based' policy-making approach were used as rationales to defer political priority. Overcoming these challenges may be important to future collective action efforts attempting to generate and sustain political priority for regulatory interventions targeting obesity. Highlights: Obesity prevention requires food marketing, labelling, pricing & content regulation. We identify factors enabling & constraining political priority for such regulation. Enablers: rising obesity prevalence, state government attention, issue framing. Constraints: non-cohesive advocates, industry power, institutional norms, evidence. Overcoming these challenges will be important to future obesity prevention efforts.